2021
DOI: 10.1136/bmjgh-2020-004575
|View full text |Cite
|
Sign up to set email alerts
|

A double-edged sword—telemedicine for maternal care during COVID-19: findings from a global mixed-methods study of healthcare providers

Abstract: IntroductionThe COVID-19 pandemic has led to a rapid implementation of telemedicine for the provision of maternal and newborn healthcare. The objective of this study was to document the experiences with providing telemedicine for maternal and newborn healthcare during the pandemic among healthcare professionals globally.MethodsThe second round of a global online survey of maternal and newborn health professionals was conducted, disseminated in 11 languages. Data were collected between 5 July and 10 September 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
173
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(188 citation statements)
references
References 57 publications
10
173
3
2
Order By: Relevance
“…Several studies including Blandford et al ( 2020 ), Mbunge et al ( 2021 ), Dodoo et al ( 2021 ), Galle et al ( 2021 ) and Lam et al ( 2021 ) noted that many countries adopted digital health technologies and some still piloting telemedicine to improve access and quality of healthcare services delivery during the pandemic to reduce transmission by observing COVID‐19 social and physical distancing guidelines. However, despite the progress made toward the adoption and utilization of telemedicine technologies such as tele‐education, teleconsultation (Bitar & Alismail, 2021 ), tele‐pharmacy, tele‐laboratory (Kamulegeya et al, 2020 ), teledermatology, teleradiology, telecardiology, tele‐ophthalmology, tele‐neurology, telerehabilitation, tele‐oncology, and telepsychiatry, little is known pertaining the adoption, success, and impediments hindering the utilization of telemedicine in sub‐Saharan Africa, especially during the pandemic.…”
Section: Contribution Of the Studymentioning
confidence: 99%
“…Several studies including Blandford et al ( 2020 ), Mbunge et al ( 2021 ), Dodoo et al ( 2021 ), Galle et al ( 2021 ) and Lam et al ( 2021 ) noted that many countries adopted digital health technologies and some still piloting telemedicine to improve access and quality of healthcare services delivery during the pandemic to reduce transmission by observing COVID‐19 social and physical distancing guidelines. However, despite the progress made toward the adoption and utilization of telemedicine technologies such as tele‐education, teleconsultation (Bitar & Alismail, 2021 ), tele‐pharmacy, tele‐laboratory (Kamulegeya et al, 2020 ), teledermatology, teleradiology, telecardiology, tele‐ophthalmology, tele‐neurology, telerehabilitation, tele‐oncology, and telepsychiatry, little is known pertaining the adoption, success, and impediments hindering the utilization of telemedicine in sub‐Saharan Africa, especially during the pandemic.…”
Section: Contribution Of the Studymentioning
confidence: 99%
“…A survey of global maternity healthcare providers utilising telemedicine during the pandemic demonstrated a concern regarding the lower quality of care and increasing pre-existing healthcare inequalities. 14 Challenges identified by healthcare professionals to introducing telemedicine included a lack of infrastructure and technological literacy, as well as financial and language barriers. 14 A survey of Australian doctors has revealed that 42% believe changes to maternity care from COVID-19 were temporary, with only 14% believing the changes were for the better.…”
Section: Discussionmentioning
confidence: 99%
“…14 Challenges identified by healthcare professionals to introducing telemedicine included a lack of infrastructure and technological literacy, as well as financial and language barriers. 14 A survey of Australian doctors has revealed that 42% believe changes to maternity care from COVID-19 were temporary, with only 14% believing the changes were for the better. 2 Furthermore, a systematic review identified numerous issues, including poor digital literacy and cost of technology which require addressing before the implementation of effective digital health.…”
Section: Discussionmentioning
confidence: 99%
“…The global pandemic prompted the maximization of telemedicine. The incorporation of telemedicine into maternal care showed a positive result in fetus development, maternal health, and obstetrics outcomes (Galle et al, 2021). Since pregnant women could doubt the credibility of online information and services and consequently feel dissatisfied, service providers and health professionals should stabilize quality and safety.…”
Section: Prenatal Care During Covid-19: General Problems and New Media Usagementioning
confidence: 99%